(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The dissemination of behavior-analytic verbal therapy gave rise to a set of investigations in behavior analysis, towards the specification of some of its dimensions. This article presents a course of investigation that aimed to develop a methodology to be used in the analysis of therapists’ verbalizations (vocal verbal responses) in behavior-analytic therapy. The article presents five studies that evaluated a system for categorization of therapists’ verbalizations, based on their possible basic functions. The quality of the system was assessed through an index of agreement between participants. Variables manipulated in the studies included characteristics of the categorization system, experience of the participants with the task, familiarity of participants with others’ categorization, type and amount of training, and complexity of the sessions. Results showed that: a) training favors indexes of agreement often higher than 70%, which suggest that the system of categorization is somewhat consistent; b) categories Investigate and Confront show higher indexes of agreement, and a greater proportion of them in the set of categorized verbalizations explain the best indexes of agreement reached; c) the process of assessing agreement through a comparison of categorizations of two participants may result in indexes that do not reflect the quality of the system of categorization. Characteristics of the categorized material, as well as of the categorizing process are mentioned as obstacles to indexes of agreement higher than 70%. They also suggest that methodological features may account for high indexes found in some studies.